1970
DOI: 10.1017/s0021859600016877
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility and chemical composition of fractions of lucerne during spring and summer

Abstract: Bulk harvests of primary growth were made at intervals during the spring and summer of 2 consecutive years from an ungrazed area of lucerne (Medicago sativa) and the digestibility by sheep was measured. At the same times, shoots of known length representative of the sward were collected, divided into 7-5 cm lengths, and separated into leaf and stem for the determination of ash, nitrogen, cellulose, and in vitro organic matter digestibility.Digestibility and leaf: stem ratio of the bulk harvests decreased and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1977
1977
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 20 publications
(18 reference statements)
0
7
0
1
Order By: Relevance
“…Several studies have reported greater decrease in forage quality in lucerne stems than in leaves with advanced phenology (Marten et al, 1988). Although differences in quality can be found between basal and apical portions of the stem throughout the growing season (Christian, Jones, & Freer, 1970), the quality of the stem as a whole organ is a matter of concern in the improvement of feeding value (Julier & Huyghe, 1997;Lenssen et al, 1991), given its large propor- This study confirmed earlier observations on the close relationship between environment DM yield and stem height in lucerne (Pembleton, Donaghy, Volenec, Smith, & Rawnsley, 2010;Volenec, Cherney, & Johnson, 1987) and the reduction in stem length and number of internodes caused by drought stress (Afsharmanesh, 2009;Sheaffer et al, 1998). The moisture-favourable Env3 exhibited the top values for stem length and forage yield.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported greater decrease in forage quality in lucerne stems than in leaves with advanced phenology (Marten et al, 1988). Although differences in quality can be found between basal and apical portions of the stem throughout the growing season (Christian, Jones, & Freer, 1970), the quality of the stem as a whole organ is a matter of concern in the improvement of feeding value (Julier & Huyghe, 1997;Lenssen et al, 1991), given its large propor- This study confirmed earlier observations on the close relationship between environment DM yield and stem height in lucerne (Pembleton, Donaghy, Volenec, Smith, & Rawnsley, 2010;Volenec, Cherney, & Johnson, 1987) and the reduction in stem length and number of internodes caused by drought stress (Afsharmanesh, 2009;Sheaffer et al, 1998). The moisture-favourable Env3 exhibited the top values for stem length and forage yield.…”
Section: Discussionmentioning
confidence: 99%
“…The leaves of this perennial legume contain little lignified tissue; however, the older parts of the stems of the plant are highly lignified, and constitute a considerable proportion of the biomass of the crop (Christian, Jones & Freer, 1970). The biosynthesis of lignin in plants occurs via a pathway which is one of several branching from general phenylpropanoid metabolism, and most enzymes of this branch pathway have been identified (Fig.…”
Section: Identification Of the Traitmentioning
confidence: 99%
“…The 20% decline in digestibility during a 12-day duration is consistent with the findings of Alder & Minson (1963) who measured a 7% decline following 1 day of grazing by steers. Most of this decline can be attributed to preferential selection of highly digestible parts by the sheep (Terry & Tilley 1964;Christian et al 1970) but may also be associated with a greater decline in levels of soluble carbohydrates in the stem over the longer grazing duration. There is a link between digestibility of stems and levels of soluble carbohydrate (Bailey et al 1970).…”
Section: Leaf:stem Ratiomentioning
confidence: 99%